If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b + 3 = 3b + 1 Reorder the terms: 3 + b = 3b + 1 Reorder the terms: 3 + b = 1 + 3b Solving 3 + b = 1 + 3b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-3b' to each side of the equation. 3 + b + -3b = 1 + 3b + -3b Combine like terms: b + -3b = -2b 3 + -2b = 1 + 3b + -3b Combine like terms: 3b + -3b = 0 3 + -2b = 1 + 0 3 + -2b = 1 Add '-3' to each side of the equation. 3 + -3 + -2b = 1 + -3 Combine like terms: 3 + -3 = 0 0 + -2b = 1 + -3 -2b = 1 + -3 Combine like terms: 1 + -3 = -2 -2b = -2 Divide each side by '-2'. b = 1 Simplifying b = 1
| 10a+1=8a+9 | | 3c-2=2c+4 | | -x^2+3x-1=0 | | (5-2x)+(4x-13)=2 | | 2b-7=b-3 | | x-3+9(8-6)= | | 3a+1=a+7 | | 5.6+1.6= | | 35-5x=4x+20 | | 4x+7=-48-7x | | 176-7x=20x+23 | | (3z+8)(5+z)=0 | | 10-8x=33-15x | | 12x+11=-109-7x | | 6b-3=-9 | | 12y-(y+5)=10y-1 | | 5x^2-10x-3.14=0 | | Y=2x^3-x+8 | | 8x+14=4x+94 | | 49-2x=7x+12 | | 9-8x=99-43x | | 5-x=4x+40 | | 8x-4=5x+32 | | 5x-7=-27 | | 5x+7=28-2x | | 7x=3x+32 | | 5x-2=30 | | -6y^2+11y-10=0 | | -4+3q=22 | | 2p-6=22 | | 2p+3=22 | | z^2+98z-64=0 |